STRATEGI PENINGKATAN KUALITAS MAHASISWA CALON GURU - Ani, Yubali; Siahaan, Meri Fuji; Tarigan, Musa Sinar (Universitas Muhammadiyah Semarang, 2017)
he purpose of this study is to describe the strategy of improving the quality of prospective teachers. The population of this study are third semester students of Faculty of Education - Universitas Pelita Harapan. A purposive sampling was taken from six study programs inUniversitas Pelita Harapan. The techniques used were questionnaires and written interviews. The qualitative data analyzed descriptively using a descriptive statistical technique. The results of this study illustrate the quality of prospective teachers from the five study programs for the KKG had a good score or 4.23, the KKSG had a good score or 4.11, and the KKMG had a good score or 3.97.Achievement of the quality of prospective teachers is obtained through the strategy used by students during the teaching and learning, such as spiritual activities that support the achievement of the KKG category; lecture activities and campus organization activities that support the achievement of KKSG category; and activities conducted on campus or off campus such as teaching that support the achievement of KKMG category. Achievement of the results of this study is expected to be applied by educational the institutions that educate prospective teachers during this study period, so that it can provide a better impact for the quality of education in Indonesia.Keywords: Teacher educational strategy, quality of prospective teachers, teacher, competences.